Based on virtual beamforming cooperative jamming with Stackelberg game for physical layer security in the heterogeneous wireless network - Shuanglin Huang; Li Zhu; Sanjun Liu (EURASIP Journal on Wireless Communications and Networking, 2018)
Abstract The physical layer security technology is a technical scheme developed in recent years to solve the problem of information security transmission in wireless communication networks. As one of the physical layer security technologies, cooperative jamming often requires collaborative nodes to actively cooperate with other nodes with secure communication requirements to transmit information. In the environment of heterogeneous wireless network, each wireless node is relatively independent, the relationship is both cooperative and competitive, and the nodes are selfish. In this paper, we study the information transmission between the source and destination nodes, and form a virtual beamforming through the cooperation of the jamming nodes to point to the malicious wiretap nodes, so as to achieve the physical layer secure communication. First, the interest distribution relationship between the source node and other cooperative interference nodes is modeled as the Stackelberg game. The source node pays the consumption of the power consumed by the cooperative jamming nodes and motivates the cooperative interference nodes to participate actively. Then, the competition relationship among all the cooperative nodes is built as a non-cooperative game, so as to promote the reasonable pricing of the consumed power when each node participates in collaboration. When the security rate between the source node and destination node is constant, the power allocation of source and cooperative nodes and the equilibrium point of power price exist and are unique. Through the combined optimization of the two games, the power pricing and power allocation can be dynamically optimized according to the change of the network environment. The simulation results show that the power dynamic allocation and power dynamic pricing have good convergence, and the source node provides a train of thought for the selection of cooperative nodes and their number.